2012
DOI: 10.1158/1940-6207.capr-11-0502
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents the Development of Oral Squamous Cell Carcinomas from Carcinogen-Induced Premalignant Lesions

Abstract: Head and neck squamous cell carcinoma (HNSCC) is a major public health concern. The recent identification of the mammalian Target of Rapamycin Complex 1 (mTORC1) signaling pathway as a highly prevalent molecular signature underlying HNSCC pathogenesis has provided the foundation to search for novel therapeutic approaches to prevent and treat HNSCC. Here, we asked whether metformin, the most widely used medication for the treatment of type 2 diabetes, which acts in part by stimulating the AMP-activated protein … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
123
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 41 publications
14
123
0
1
Order By: Relevance
“…Several studies have provided evidence about this relationship, but most of them have been in vitro or in vivo animal studies [45,46]. We found only 3 prospective cohort studies for inclusion in this review, and all of them supported an association between metformin and decreased risk of HNSCC [9,20,21].…”
Section: Summary Of Evidencementioning
confidence: 92%
See 1 more Smart Citation
“…Several studies have provided evidence about this relationship, but most of them have been in vitro or in vivo animal studies [45,46]. We found only 3 prospective cohort studies for inclusion in this review, and all of them supported an association between metformin and decreased risk of HNSCC [9,20,21].…”
Section: Summary Of Evidencementioning
confidence: 92%
“…We identified 11 articles with experimental studies that were in vitro and in vivo animal studies that analyzed the effect of metformin in HNSCC [20,28,45,46,[49][50][51][52][53][54][55] 2 of these studies presented the most important and complete results. Vitale-Cross et al [46] showed that metformin reduced the growth of HNSCC cells and diminished their mTORC1 activity by both AMPK-dependent and AMPK-independent mechanisms.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Jüngste Studien belegen, dass die Einnahme von Metformin bei DM-Patienten sowohl das Risiko für eine Krebserkrankung verringert als auch die Prognose verbessert [6,7,9]. Zusätzlich führt die Applikation von Metformin zu einer signifikanten Reduktion spontaner Konvertierungen von proliferierenden Epithelschichten aus oralen, prämalignen Läsionen in ein Plattenepithelkarzinom [32]. Jedoch wurde für Diabetes Typ 2 bislang lediglich eine inverse Assoziation mit HNSCC festgestellt [26].…”
Section: Diabetes Mellitus Als Prognostischer Marker Beim Oropharynxuunclassified
“…For example, metformin might regulate tumorigenesis through the systemic reduction of growth factor insulin and the induction of energetic stress by oxidative phosphorylation [55]. For HNSCC, metformin administration was effective to modulate cell growth via global protein translational regulation in vitro as well as to inhibit mTORC1-mediated cell proliferation in oral epithelial basal cells in vivo implying its significance as anti-neoplastic and anti-diabetic medication in DM patients with HNSCC [56,57]. Interestingly, a very recent study found that metformin facilitated autophagy and triggered apoptosis by down-regulation of oncogenic factor STAT3, one of the glycemia-mediated regulators revealed using the protein array in this study (Supplementary Figure S4B), in esophageal SCC [58] further suggesting potential interplays between different glycemic oncotargets.…”
Section: Discussionmentioning
confidence: 99%